Effects of nitrogen on the growth of Misai Kucing (Orthosiphon stamineus) - Rozilawati Mohd Azman.
Misai kkucing (Orthosiphon stamineus) is identified amongst the most potential herbs to be commercialized in Malaysia, thus more detailed information on nutrients uptake is required to increase the yield. An experiment on the effects of nitrogen on the growth of misai kucing was conducted at Ladang 2, UPM, under rain shelter. Plants were grown in 61/2 cm post, filled with cocoa peat sand mixture (3:1 v/v). The treatment consisted of three rates of nitrogen, 100, 200 and 300 mg/L. Modified Cooper nutrient formulation was used to supply the nutrients. Treatments were arranged in Completely Randomized Design (CRD). Plants were harvested after two months. Results from this study indicated that there were highly significant effects of different rates of nitrogen on plant canopy, root: shoot ratio, photosynthetic rate and acid ascorbic content, as well as N and K contents in leaf tissue. For total leaf area, specific leaf area, total P and Ca contents in leaf tissue, significant effect was observed between treatment levels. Since there was no significant difference observed on total dry weight of shoot and leaf is the most used commercially, 200 mg/L N is the optimum and effective rate which can be applied based on plant canopy, total leaf area, specific leaf area, root: shoot ratio and photosynthetic rate.